Why Nepal Matters in the Geopolitical Chessboard - Poudyal, Biranchi (Unity Journal, 2022)
This study examines the position of Nepal in the geopolitical chessboard amid the participation of international actors, including; China, America, and India’s sphere of influence. It argues that the involvement of international actors in Nepal with their strategy-loaded projects like BRI and MCC has put Nepal under the pressure to accommodate the geopolitical interest of both superpowers by adhering to its policy of non-alignment. The research further aims to identify the new geopolitical paradigm of Nepal and its growing significance in the geopolitical chessboard. After analyzing the available literature and the arguments of scholars, this paper found that Nepal has now become a land of geo-strategic importance that belies its weakness as a small state. This finding supports the conclusion that the external forces are taking interest in Nepal mainly because of its geographical positioning that gives them the advantage of connectivity potential, the balance of power, sphere of influence, and security outlook.